2021
DOI: 10.33774/chemrxiv-2021-5twk7-v3
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Design, Synthesis and Biological Evaluation of Novel SARS-CoV-2 3CLpro Covalent Inhibitors

Abstract: Severe diseases such as the ongoing COVID-19 pandemic, as well as the previous SARS and MERS outbreaks, are the result of coronavirus infections and have demonstrated the urgent need for antiviral drugs to combat these deadly viruses. Due to its essential role in viral replication and function, 3CLpro> has been identified as a promising target for the development of antiviral drugs. Previously reported SARS-CoV 3CLpro non-covalent inhibitors were used as a starting point for the development of covalent inhi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 51 publications
0
3
0
Order By: Relevance
“…FITTED has been initially developed and optimized for protein targets and has been applied to the discovery of a number of enzyme inhibitors. [24][25][26] Following these successful prospective validations, we sought to evaluate FITTED on nucleic acids. Prior to its application, we modified our program to account for nucleic acids and challenged it for the discovery of small molecules binding RNA motifs.…”
Section: Docking To Riboswitchesmentioning
confidence: 99%
“…FITTED has been initially developed and optimized for protein targets and has been applied to the discovery of a number of enzyme inhibitors. [24][25][26] Following these successful prospective validations, we sought to evaluate FITTED on nucleic acids. Prior to its application, we modified our program to account for nucleic acids and challenged it for the discovery of small molecules binding RNA motifs.…”
Section: Docking To Riboswitchesmentioning
confidence: 99%
“…In 2021, Moitessier research group transformed the non-covalent inhibitor 96 acting on SARS-CoV-1 M pro into covalent inhibitors acting on SARS-CoV-2 M pro [ 95 ]. The study of the crystal structure shows that compound 96 might be modified by adding a covalent warhead near the catalytic cysteine residue.…”
Section: The Development Of Sars-cov-2 M Pro Inhib...mentioning
confidence: 99%
“…The docking poses confirmed that the reactive group substituting the imidazole ring should lead to effective covalent inhibition. It is satisfactory that the inhibitory efficacy of the lead compounds 97 and 98 developed by them is an order of magnitude higher than that of compound 96 [ 95 ].…”
Section: The Development Of Sars-cov-2 M Pro Inhib...mentioning
confidence: 99%